Effort to Maximize Profit and Optimize Both Time and Business Capital Resources Through The Determination of Many Small, Medium and Large Packing Units In The "ENY" Tempe Chips Home Industry - Susanto, Lukas (International Journal of Social Service and Research, 2021)
Tempe chips are a superior product in Ngawi Regency. Some home-industries of tempe chips have also been negatively affected by the COVID-19 pandemic, including a decline in sales, difficulties in raw materials, capital problems and obstacles to the production process. Various efforts to increase sales have been carried out both through mentoring and research, among others by trying to do online marketing and designing better tempe chips packaging designs, but there has been no good planning on product composition. From the interview, it is known that in determining the composition of the many packaging units of tempe chips and determining the selling price per unit, it is only based on experience while running a business and no optimization method has been used. Therefore, it is necessary to apply an optimization method to obtain maximum profit. In this research, we try to determine the number of production units for each type of tempe chips packaging that produces maximum profit and determine efficiency in the use of cost and time resources. Data collection techniques are carried out by observation and interviews. . We found that the home industry reached the maximum profit at 661 units of small packaging and 269 units of large packaging which gained IDR 23600 and time was reduced to 9.29 h